Effects of Emotional Labor on Organizational Citizenship Behaviors of Secondary Vocational Teachers: A Cross-Level Moderation Intermediary Model - Hao, Qiang; Yu, Shun-Chi (International Journal of Multidisciplinary in Management and Tourism, 2022)
This article aimed to study the connection between emotional labor and organizational citizenship behaviors. Emotional labor as a mental behavior to control emotional attrition has received much attention in scholarly practice. Existing research revolves around the role of organizational citizenship behavior as a direct influence on emotional labor, but lacks an examination of the specific mechanisms by which emotional labor acts on organizational citizenship behavior. This study explored the mechanisms of emotional labor's impact on organizational citizenship behavior through a cross-level study of data from 350 secondary vocational teachers. This study finds that emotional labor significantly and negatively affects organizational citizenship behavior. The study also clarifies that the psychological contract mediates emotional labor and organizational citizenship behavior. Organizational support positively moderates the mediating effect of the psychological contract on the relationship between emotional labor and organizational citizenship behavior.